Analysis of Body Posture using Rapid Entire Body Assessment (REBA) and Rapid Upper Limb Assessment (RULA) to Improve the Posture of Sand Paper Machine Operators and Reduce the Risk of Low Back Pain - Trio Yonathan Teja Kusuma (Biology, Medicine, & Natural Product Chemistry, 2020)
The metal casting industry, Nitikan is a micro business whose production process is carried out manually. The equipment used is simple and without considering the user's health. This can be seen in the product finishing process that uses a sanding machine. The equipment is not designed according to the user's posture so the operator bends in doing work movements, of course this is very risky to experience lower back pain injuries. This study aims to analyze the work activities of the finishing process using the Rapid Entire Body Assessment (REBA) and Rapid Upper Limb Assessment (RULA) approach and design work tools that can be applied to improve work posture. The results of data processing and analysis obtained a Rapid Entire Body Assessment score on a sandpaper machine single head of 5 and a Rapid Upper Limb Assessment score of 4, the score indicates that the work position has the potential to experience a risk of low back pain, so there must be an improvement in work posture. Work posture improvement is done by designing a tool in the form of a sandpaper machine that takes into account ergonomic dimensions to reduce the risk of lower back injury. The final result after the improvement is obtained Rapid Entire Body Assessment score of 3 and Rapid Upper Limb Assessment score of 4. This shows that the risk of lower back injuries can be minimized.